Postural Control While Sitting and Its Association with Risk of Falls in Patients with Parkinson's Disease - Hayashi, Ryoichi; Hayashi, Takeshi; Aizawa, Junpei; Nagase, Hiroaki; Ohara, Shinji (IntechOpen, 2011)
None